KARAKTERISTIK PEMIKIRAN DAN CORAK GERAKAN DAKWAH PONDOK PESANTREN - Wawan Trans Pujianto (Ath Thariq Jurnal Dakwah dan Komunikasi, 2017)
Symptoms of the trend of pesantren today also appear in the urban environment, such as the phenomenon of some pesantren students or students, such as in Malang, Al-Hikam, UlilAbsor, Firdaus, Dar al-Hijrah, and others. This trend shows that, although the pesantren education system has some weaknesses, it is still considered the most effective place to introduce Islam. Based on the condition of pesantren in such a way, then the concept of pesantren become a reflection of society thinking in educating and doing social change to society. Through this study, it is expected to give positive contribution in the form of information about the development of pesantren and the characteristics of thought and style of dakwah movement of pesantren to be socialized tothe community, especially the suggestion and recommendation and to support the development of pesantren in Indonesia.